Ghosts of Sheridan Circle : How a Washington Assassination Brought Pinochet's Terror State to Justice - McPherson, Alan L. (Book collections on Project MUSE., 2019)
"On September 21, 1976, Embassy Row in Washington, D.C. shook from a car bomb explosion, the only act of state-sponsored terrorism in the city's history. The leading opponent of the dictator Augusto Pinochet, former Chilean ambassador to the United States Orlando Letelier, along with a U.S. colleague, Ronni Moffitt, died within minutes of the blast at Sheridan Circle, in the heart of D.C. Authorities determined that the assassination had been planned by DINA, the secret police of Chile. McPherson chronicles the nineteen-year investigation and prosecution of the Letelier case, which pitted Washington's investigative agencies and civil society against recalcitrant U.S. chief executives. The FBI, Department of Justice agents, and mid-level diplomats grew frustrated by the unwillingness of Presidents Nixon, Ford, Carter, and Reagan to confront Pinochet, an ally in the Cold War. Pledging to do their jobs, these federal agents allied with activists and with Orlando Letelier's widow, Isabel, to pursue the case no matter where it led--from the prisons of Venezuela, to Cuban-American bars in New Jersey, to the secret police prisons and Supreme Court of Chile. Working on the case from the 1970s to the 1990s, they secured convictions of all the killers of Letelier and Moffitt"--